Benzoimidazole‐Pyridylamido Zirconium and Hafnium Alkyl Complexes as Homogeneous Catalysts for Tandem Carbon Dioxide Hydrosilylation to Methane. Issue 1 (26th April 2018) - Luconi, Lapo; Rossin, Andrea; Tuci, Giulia; Gafurov, Zufar; Lyubov, Dmitrii M.; Trifonov, Alexander A.; Cicchi, Stefano; Ba, Housseinou; Pham‐Huu, Cuong; Yakhvarov, Dmitry; Giambastiani, Giuliano
Abstract: Neutral Zr IV and Hf IV alkyl/amido complexes stabilized by a tridentate N ligand that contains a "rolling" heterodentate benzoimidazole fragment have been prepared and characterized. The ultimate nature of the ligand denticity, the electronic properties of the ligand binding pocket and the metal coordination environment are controlled by the protection/deprotection of the benzoimidazole NH group. The metal precursor used [M IV (Bn)4 or M IV (NMe2 )4 ] also has an influence on the final coordination sphere of the complex; indeed, a permanent central pyridine dearomatization occurs in the presence of dimethylamido ancillary groups. DFT calculations on the real system have been used to elucidate the mechanism. Selected alkyl species from this series have been scrutinized for the tandem hydrosilylation of CO2 to CH4 in combination with the strong Lewis acid B(C6 F5 )3 using a variety of hydrosilanes. A positive effect of the hardness modification of the ligand donor atom set is observed in the catalytic outcomes. Indeed, κ 3 N −, N, N − Zr IV (Bn)2 catalyzes the process to methane selectively with a turnover frequency as high as 272 h −1 (at 96 % substrate conversion) almost twice as much as that claimed for the benchmark κ 3 O −, O, O − Zr IV (Bn)2 complex under similar experimental conditions. Abstract : Working in tandem : Zr IV /Hf IV alkyl coordination compounds stabilized by a N ligand that contains a "rolling" heterodentate benzoimidazole fragment are prepared and employed with B(C6 F5 )3 for mild CO2 hydrosilylation to methane. The modification of the hardness of the ligand donor atom set translates into a better catalytic performance with respect to that of the benchmark catalytic system.